Dicarbonyl[10,10-dimethyl-5,15-bis(pentafluorophenyl)biladiene]ruthenium(II): discovery of the first ruthenium tetrapyrrole cis-dicarbonyl complex by X-ray and electron diffraction - Pham, Trong Nhan; Shirley, Hunter; Merkelbach, Johannes; Gurung, Kshitij; Palatinus, Lukáš; Yap, Glenn P A; Rosenthal, Joel (Acta crystallographica. Section C, Structural chemistry, 2024)
Dicarbonyl[10,10-dimethyl-5,15-bis(pentafluorophenyl)biladiene]ruthenium(II), [Ru(C33H16F10N4)(CO)2] or Ru(CO)2[DMBil1], is the first reported ruthenium(II) cis-dicarbonyl tetrapyrrole complex. The neutral complex sports two carbonyls and an oligotetrapyrrolic biladiene ligand. Notably, the biladiene adopts a coordination geometry that is well distorted from square planar and much more closely approximates a seesaw arrangement. Accordingly, Ru(CO)2[DMBil1] is not only the first ruthenium cis-dicarbonyl with a tetrapyrrole ligand, but also the first metal biladiene complex in which the tetrapyrrole does not adopt a (pseudo-)square-planar coordination geometry. Ru(CO)2[DMBil1] is weakly luminescent, displaying λem = 552 nm upon excitation at λex = 500 nm, supports two reversible 1 e- reductions at -1.45 and -1.73 V (versus Fc+/Fc), and has significant absorption features at 481 and 531 nm, suggesting suitability for photocatalytic and photosensitization applications. While the structure of Ru(CO)2[DMBil1] was initially determined by X-ray diffraction, a traditionally acceptable quality structure could not be obtained (despite multiple attempts) because of consistently poor crystal quality. An independent structure obtained from electron diffraction experiments corroborates the structure of this unusual biladiene complex.
Keywords: crystal structure; ruthenium; reduction photocatalyst; electron diffraction; tetrapyrrole; biladiene